Chondrites isp. Indicating Late Paleozoic Atmospheric Anoxia in Eastern Peninsular India - Biplab Bhattacharya; Sudipto Banerjee (The Scientific World Journal)
Rhythmic sandstone-mudstone-coal succession of the Barakar Formation (early Permian) manifests a transition from lower braided-fluvial to upper tide-wave influenced, estuarine setting. Monospecific assemblage of marine trace fossil Chondrites isp. in contemporaneous claystone beds in the upper Barakar succession from two Gondwana basins (namely, the Raniganj Basin and the Talchir Basin) in eastern peninsular India signifies predominant marine incursion during end early Permian. Monospecific Chondrites ichnoassemblage in different sedimentary horizons in geographically wide apart (~400 km) areas demarcates multiple short-spanned phases of anoxia in eastern India. Such anoxia is interpreted as intermittent falls in oxygen level in an overall decreasing atmospheric oxygenation within the late Paleozoic global oxygen-carbon dioxide fluctuations.